UPAYA PERBAIKAN KEANDALAN ROLLER MILL DENGAN ROOT CAUSE ANALYSIS DAN PENDEKATAN PREVENTIVE MAINTENANCE - Budiharjo Budiharjo; Zulfa Fitri Ikatrinasari (JURNAL TEKNIK INDUSTRI, 2016)
In order to meet the increasing needs of electricity and steam, PT. DSS seeks to maintain thecontinuity of the process of generation and distribution, by maintaining reliability of Roller Millsystem. Based on the historical damage of the Roller Mill, then conducted this study with the aim ofimproving reliability of the Roller Mill system. Search root cause of the problem using the method ofCause and Effect Diagram and Root Cause Analysis, and corrective actions with preventivemaintenance approach. Secondary data such as operation time, down time and frequency of damageof the Roller Mill system, sourced from maintenance data of Mechanical Section. From the analysisfound that the root cause of problems-Tip Plow damage is the cause of damage spare part RollerMill. Maintenance activities with the implementation of preventive maintenance has improved thereliability of the Roller Mill system with an increase of 6.90% Operational Availability.